2004
DOI: 10.1124/jpet.104.073494
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Induces Apoptosis in Fetal Rat Myocardial Cells through the p38 Mitogen-Activated Protein Kinase and Mitochondrial/CytochromecPathways

Abstract: Cocaine induces apoptosis in fetal rat myocardial cells (FRMCs). However, the mechanisms are not clear. The present study examined the role of p38 mitogen-activated protein kinase (MAPK) and cytochrome c release in the cocaine-induced apoptosis in primary culture of FRMCs prepared from the fetal heart of gestational age of 21 days. Cocaine induced timedependent, concurrent increases in cytochrome c release and activities of caspase-9 and caspase-3, which preceded apoptosis. Caspase-8 was not activated. In acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 58 publications
2
44
0
Order By: Relevance
“…Cocaine-elicited apoptosis has been observed in rat fetal locus coeruleus neurons, myocardial and vascular smooth muscle cells, mouse hepatocytes, and human epithelial cells of nasal mucosa [55][56][57][58][59]. For example, in fetal rat myocardial cells, p38alpha mitogen-activated protein kinase (MAPK) plays an important role in the cocaine-induced apoptosis by promoting cytochrome c release [58]. It would then be of interest to apply MAPK inhibitors to observe if cocaine-induced vacuolation could be blocked and apoptosis be inhibited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cocaine-elicited apoptosis has been observed in rat fetal locus coeruleus neurons, myocardial and vascular smooth muscle cells, mouse hepatocytes, and human epithelial cells of nasal mucosa [55][56][57][58][59]. For example, in fetal rat myocardial cells, p38alpha mitogen-activated protein kinase (MAPK) plays an important role in the cocaine-induced apoptosis by promoting cytochrome c release [58]. It would then be of interest to apply MAPK inhibitors to observe if cocaine-induced vacuolation could be blocked and apoptosis be inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cocaine can induce cell death by either apoptotic or necrotic pathway [55][56][57][58][59][60][61][62][63]. Cocaine-elicited apoptosis has been observed in rat fetal locus coeruleus neurons, myocardial and vascular smooth muscle cells, mouse hepatocytes, and human epithelial cells of nasal mucosa [55][56][57][58][59]. For example, in fetal rat myocardial cells, p38alpha mitogen-activated protein kinase (MAPK) plays an important role in the cocaine-induced apoptosis by promoting cytochrome c release [58].…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen activated protein (MAP) kinases are a family of protein kinases associated with genes encoding stress, apoptotic response factors which determines the fate of the cardiomyoctes to undergo either survival or death in the myocardium [13].…”
Section: Introductionmentioning
confidence: 99%
“…20,22,25,28 The stereotypical unkempt appearance of many street SUD patients is well known. However, the existence of a signifi cant literature demonstrating that addictive drugs impair cell growth 29 on the one hand and stimulate cellular apoptosis [30][31][32][33][34] on the other, suggests that it is theoretically conceivable that substance dependence might actually be accelerating the ageing process in accordance with the cellular hypothesis of ageing. 35,36 Indeed, the ageing process itself has increasingly been characterised as a stem cell disorder.…”
Section: Researchmentioning
confidence: 99%